Smoke on the water: A case report of chronic renal failure resulting from the ingestion of smoke machine fluid. (February 2017) - Trimble, Alice; Partridge, Richard
We report the case of an 18-year-old male admitted to the Intensive Care Unit in Basingstoke and North Hampshire Hospital, who developed chronic kidney disease following the ingestion of smoke machine fluid. Smoke machine fluid may contain ethylene glycol, and a diagnosis of ethylene glycol toxicity with calcium oxalate nephropathy was made. This case resulted in a National Poisons Information Service internal review of the subject and a new TOXBASE entry for smoke machine fluid ingestion.